Recommender system based on argumentation by analogy - Budán, Paola D. (2014)
Argumentation has contributed to the formalization of a reasoning model, similar to the human reasoning. In general, argumentation can be associated with the interaction of reasons in favour and against certain conclusions, so as to determine what conclusions are acceptable. A way of arguing in which the way in which the arguments are constructed, is Defeasible Logic Programming (DeLP); this is a formalism that combines logic programming and defeasible argumentation. This work focuses on the strengthening of the reasoning process, identifying partial connections or determinations between knowledge pieces. Through these relations, it is possible to increase the justi cations and foundations that support a particular recommendation, by an analogy process.